1992
DOI: 10.1007/bf02220608
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for analgesia mediated by peripheral opioid receptors in inflamed synovial tissue

Abstract: Intra-articular morphine (5 mg in 25 ml) was administered to patients for post-operative analgesia following arthroscopic knee surgery. At various time intervals, 30 min to 4 h post morphine, venous blood samples were taken in order to determine plasma levels of morphine and its primary metabolites, morphine-3-glucuronide and morphine-6-glucuronide. Measurable amounts of morphine and morphine-3-glucuronide were found in the plasma of 7/10 patients whereas morphine-6-glucuronide was detected in only 2/10 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…On the other hand, we found neostigmine and clonidine more effective than tenoxicam, supporting Buerkle et al [14] who had reported that, despite the similarities between opioid and muscarinic analgesia, the analgesic efficacy of neostigmine was not altered by inflammation. Intraarticularly administered opoids produce analgesia by binding peripheral opioid receptors which have been found in synovial biopsies from knee joint [2,22]. The most popular opioid for i.a route is morphine, which provides dose-and time-dependent analgesia [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found neostigmine and clonidine more effective than tenoxicam, supporting Buerkle et al [14] who had reported that, despite the similarities between opioid and muscarinic analgesia, the analgesic efficacy of neostigmine was not altered by inflammation. Intraarticularly administered opoids produce analgesia by binding peripheral opioid receptors which have been found in synovial biopsies from knee joint [2,22]. The most popular opioid for i.a route is morphine, which provides dose-and time-dependent analgesia [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…However, 60% of 5 mg preoperative morphine patients and 50% of 5 mg postoperative patients did not require any postoperative analgesic [22] in a clinical study, in which low doses of intra-articular morphine provided better pain control than systemic morphine administration, and this effect was reversible by administering the intra-articular opioid antagonist naloxone. The existence of opioid receptors has been demonstrated in synovial biopsies [15].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have demonstrated anti-inflammatory effects Lindegaard et al, 2010b) and a lack of local tissue toxicity (Todhunter et al, 1996;Tulamo et al, 1996;Jaureguito et al, 2002). After intra-articular injec-PERIPHERAL PAIN INHIBITION tion, morphine was detectable in synovial fluid for up to 24 h but did not reach clinically significant concentrations in the systemic circulation (Lawrence et al, 1992;Tulamo et al, 1996;Richardson et al, 1997;Brandsson et al, 2000;Lindegaard et al, 2010a).…”
Section: A Treatment Of Pain and Inflammationmentioning
confidence: 99%